1996
DOI: 10.1126/science.272.5265.1163
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Flux of Biogenic Carbon in the Ocean: Is There Food Web Control?

Abstract: Models of biogenic carbon (BC) flux assume that short herbivorous food chains lead to high export, whereas complex microbial or omnivorous food webs lead to recycling and low export, and that export of BC from the euphotic zone equals new production (NP). In the Gulf of St. Lawrence, particulate organic carbon fluxes were similar during the spring phytoplankton bloom, when herbivory dominated, and during nonbloom conditions, when microbial and omnivorous food webs dominated. In contrast, NP was 1.2 to 161 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 35 publications
4
55
0
1
Order By: Relevance
“…With data from the GSL only, Rivkin et al [1996] concluded that unlike other systems, the gulf exports approximately the same amount of carbon to the bottom whether the surface waters are undergoing bloom or nonbloom conditions. Since the composition of the export is changing from more chlorophyllous material in bloom conditions compared to more fecal pellets in nonbloom conditions, it may well be that the LSLE is a source of biogenic carbon for the GSL throughout the summer.…”
Section: Resultsmentioning
confidence: 99%
“…With data from the GSL only, Rivkin et al [1996] concluded that unlike other systems, the gulf exports approximately the same amount of carbon to the bottom whether the surface waters are undergoing bloom or nonbloom conditions. Since the composition of the export is changing from more chlorophyllous material in bloom conditions compared to more fecal pellets in nonbloom conditions, it may well be that the LSLE is a source of biogenic carbon for the GSL throughout the summer.…”
Section: Resultsmentioning
confidence: 99%
“…A number of possible explanations for the observed correlations were evaluated as follows: There is obviously no close coupling of BSi and OM in the particle flux to the seafloor and within the sediment which could explain the correlation of Si:O 2 fluxes. Although both BSi and OM are major components of diatoms that are found in certain ratios in the living organisms (Ragueneau et al, 2000, the biogeochemical cycles of silicon and carbon decouple both vertically and horizontally in the water column (Rivkin et al, 1996;Gallinari et al, 2002;Ragueneau et al, 2002). Considering the multitude of water depths, and the different regions investigated, related concentrations in the particle rain reaching the seafloor are highly unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Past attempts to determine carbon flux simplistically as a function of primary production have consistently met with failure. So, it is now acknowledged that food web structure plays an fundamental role in regulating carbon flux (Rivkin et al, 1996). The discovery of TEP and their role in the aggregation of particles has now further improved our understanding of the biogeochemical cycling of carbon.…”
Section: Changing Conceptsmentioning
confidence: 99%
“…Which fraction of primary produced particles sinks to depth, also depends on the type of food web present (Rivkin, Legendre, Deibel, Tremblay, Klein, Crocker et al, 1996). Particles may be utilized by bacteria or grazed by eukaryotes.…”
Section: Food-web Structurementioning
confidence: 99%